The Time and the Maps: Forms, Perceptions and Representations of the Time in Medieval Mappaemundi - Borges, Thiago (Eikón / Imago, 2016)
Having a dual essence, that transit between the realism and the symbolism, the medieval world maps disclose, by hierarchical pictorial conceptions, the existence of different temporal stratum which, on a seemingly homogeneous level, coexist and interact naturally. In this regard, from the cyclicality of human time to a linearity of sacred time, the text presented seeks to contemplate the inherent complexity of shapes and perceptions that remain written on the long design that comprise a medieval world map. We therefore hope that the analysis and the systematic comparison of these imagines mundi may disclose, beyond its iconographic aspects, assured elements for the understanding of the speech, intention and perception that permeate the representations of time and spaces in the medieval West.